An implementation evaluation of light for the world´s inclusive education programme in Ethiopia - Muellegger, Birgit (Organisational Psychology, 2021)
Inclusive education programmes aim to include children with disabilities in mainstream schools by providing quality education in a barrier-free environment. These programmes are especially necessary in developing countries, where about one-third of all children have some sort of disability. Sustainable Development Goal 4 of education for all cannot be reached when these children are left out from schooling. The following dissertation presents the findings of an implementation evaluation of an inclusive education programme in Ethiopia. The programme, One Class for All (OCFA), is financed by Light for the World, an international non-government organization (NGO), and implemented by 14 Ethiopian partner organisations. A descriptive evaluation design combining qualitative and quantitative elements was used to examine typical Light for the World programmes as delivered by partners and as they appear on the ground. The data collection mainly involved interviews of partners and participants at selected schools in Ethiopia and a survey of all implementing partners. The evaluation indicated that the composition of implementing partners and their capacity in terms of content knowledge and collaborations are working well. We nevertheless highlight some high-level opportunities to improve the inclusive education programme of Light for the World. More structured development plans for each school are required, and a better connection between Light for the World`s community-based-rehabilitation (CBR) programmes and its inclusive education programmes is necessary to support entry to school for persons with disabilities. Under these overall findings, a more structured teacher training programme, better selection of teachers, and better local networking and targeted awareness raising programmes are also needed. This evaluation contributes to the limited literature on successful inclusive education programmes in developing countries.